Математичне моделювання перехідних процесів у лінії Лехера в стані неробочого ходу - Чабан, А.В.; Левонюк, В.Р.; Дробот, І.М.; Герман, А.Ф. (Електротехніка і електромеханіка, 2016)
В работе, на основе обобщенного междисциплинарного (интердисциплинарного) метода математического
моделирования, основанного на модификации интегрального вариационного принципа Гамильтона-Остроградского,
предложена математическая модель двухпроводной длинной линии электропередач, которая работает на холостом
ходу. Представлены результаты компьютерной симуляции переходных процессов в виде рисунков, которые
анализируются. У роботі, на основі узагальненого міждисциплінарного (інтердисциплінарного) методу математичного моделювання,
який ґрунтується на модифікації інтегрального варіаційного принципу Гамільтона-Остроградського, запропоновано
математичну модель двопровідної довгої лінії електропередач, що працює в неробочому стані. Представлено
результати комп'ютерної симуляції перехідних процесів у вигляді рисунків, які аналізуються. Purpose. The work proposed for the modeling of transients in
Lehera line uses a modified Hamilton-Ostrogradskiy principle.
The above approach makes it possible to avoid the decomposition
of a single dynamic system that allows you to take into account
some subtle hidden movements. This is true for systems with
distributed parameters, which in the current work we are
considering. Methodology. Based on our developed new
interdisciplinary method of mathematical modeling of dynamic
systems, based on the principle of modified HamiltonOstrogradskiy and expansion of the latter on the non-conservative
dissipative systems, build mathematical model Lehera line. The
model allows to analyze transient electromagnetic processes in
power lines. Results. In this work the model used for the study of
transients in the non-working condition Lehera line. Analyzing
the results shows that our proposed approach and developed
based on a mathematical model is appropriate, certifying physical
principles regarding electrodynamics of wave processes in long
power lines. Presented in 3D format, time-space distribution
function of current and voltage that gives the most information
about wave processes in Lehera line at non-working condition
go. Originality. The originality of the paper is that the method of
finding the boundary conditions of the third kind (Poincare
conditions) taking into account all differential equations of
electric power system, i.e. to find the boundary conditions at the
end of the line involves all object equation. This approach enables
the analysis of any electric systems. Practical value. Practical
application is that the wave processes in lines affect the various
kinds of electrical devices, proper investigation of wave processes
is the theme of the present work